The readiness of Quezon City Public Library and its five branches in District IV to support the ALS learners for the Department of Education Accreditation and Equivalency test - Balopiños, Carlos C. (2012)
This study was conducted to know the information needs of the ALS learners from the 22 ALS Implementers in District IV of Quezon City and to determine the readiness of the Quezon City Public Library and its five branches in District IV. Furthermore, this study aimed to: (1) know which of the subjects or strands of ALS program and learners need additional materials in; (2) know which subject of the ALS program is the most difficult for the ALS learners; (3) know if the ALS learners visit the school library or the public library; (4) know how often they visit the school library and the public library, and; (5) know if ALA learners get sufficient information when they visit the school library and the public library, (6) know whether Quezon City Public Library and its five branches in District IV have information materials which correspond to the subjects in ALS program.